(untitled) (Research, Society and Development, 2024)
Background: Antipsychotic-induced akathisia poses a significant challenge in clinical practice due to its frequent oversight in diagnosis and associated severe consequences such as suicidal behavior and compromised treatment adherence. Understanding the underlying mechanisms and implementing effective management strategies are imperative in addressing this clinical concern. Objective: provide an updated understanding of the correlation between antipsychotics and akathisia, discussing its pathophysiology, diagnosis, assessment, and current as well as prospective treatment options. Methods: An integrative literature review was conducted utilizing Pubmed and Virtual Health Library databases, supplemented by additional resources to broaden the study’s scope. Results and Discussion: Among the 204 studies analyzed, 17 met the criteria for inclusion in the review, complemented by 7 articles focusing on assessment scales. The study explores the impact of neuroleptic medications on akathisia’s pathophysiology, diagnostic approaches, symptomatology, assessment tools, and management strategies. Conclusion: Robust research endeavors are crucial to consolidate evidence, identify gaps, and offer a holistic perspective on akathisia. The profound comprehension of the condition reveals paths to enhance patients’ quality of life.